Evektifitas Bantuan Langsung Tunai Dana Desa Bagi Masyarakat Terdampak Covid-19 Di Desa Puseurjaya, Kecamatan Telukjambe Timur Kabupaten Karawang - Mohamad Padli Fauzy (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study discusses the effectiveness of Village Fund Direct Cash Assistance (BLT DD) for communities affected by the COVID-19 pandemic in Puseurjaya Village, Telukjambe Timur District, Karawang Regency. This study uses a qualitative descriptive method with data collection techniques carried out in three ways, namely interviews, observation and documentation, then the data is analyzed through three stages of reduction, presentation and conclusion drawing. This study uses the theory of effectiveness of Sutrisno Edi (2019). The purpose of this study was to determine the effectiveness of BLT DD in Puseurjaya Village for communities affected by Covid-19 in terms of program understanding, target accuracy, timeliness, goal achievement and real change. The results of this study are the effectiveness in terms of timeliness because there is no delay in the disbursement of BLT DD, the accuracy of the target where the recipients of BLT DD are the people of Puseurjaya Village who have met the predetermined requirements and the achievement of the BLT DD program objectives to ease the economy of the Puseurjaya Village community. Then it has not been effective in the program understanding sector due to the lack of Puseurjaya residents who understand well the BLT DD program and real changes because the community has not been wise in using BLT DD money in their daily lives and there is no guidance from the Puseurjaya village government after the disbursement of BLT DD.